The Effect of Wordwall Media Use on The Science Learning Outcomes Of Grade IV Students - Sinaga, Harry Jason; Sihombing, Lisbet N.; Sidabutar, Yanti Arasi (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to determine the effect of using wordwall media on the social studies learning outcomes of fourth-grade students at SD Negeri 091544 Pardomuan in the 2025/2026 academic year. This study employed a quantitative approach with a one-group pretest-posttest design. The sample consisted of 21 fourth-grade students at SD Negeri 091544 Pardomuan. The instrument used was multiple-choice questions. Statistical data analysis using the N-Gain test showed that most students experienced an increase in understanding, with an average N-Gain score of 0.6473 and an average N-Gain percentage of 64.7255%, making it categorized as quite effective. Therefore, it can be concluded that the use of wordwall media significantly improved student learning outcomes in fourth-grade students at SD Negeri 091544 Pardomuan in the 2025/2026 academic year